ANALISIS RESEPSI KONTEN PADA AKUN TIKTOK @VMULIANATERHADAP KEBUTUHAN INFORMASI AKAN CAREER PREPARATION - Firly Aldrina Putri (2023)
This study aims to examine the audience's meaning of information about careers on TikTok accounts through the reception study of Stuart Hall. Researchers focus on the content of the TikTok @vmuliana account regarding the career preparation needed by the younger generation, especially students regarding how to make a good CV to the interview process. This study uses the reception analysis method using primary and secondary data sources which aims to examine how individuals interpret and understand career education content displays on the TikTok @vmuliana account in fulfilling their information needs for career preparation. The sampling technique uses purposive sampling and uses 3 main elements in the reception methodology, such as the collection, analysis, and interpretation of reception data. The validity of the data was carried out by researchers using a type of source triangulation. Resource persons can be categorized into Stuart Hall's interpretive position, namely Dominant Hegemonic Position, Negotiated Position, and Oppositional Position. The results of this study show that of the five informants, 2 informants were found to be in the Dominant position and 3 informants were in the Negotiation position. The existence of different meanings conveyed by the informants was influenced by differences in the background of each informant, such as educational background, life experience, and the level of knowledge of a person in meeting their information varies needs for career preparation.